An updated radiocarbon-based ice margin chronology for the last deglaciation of the North American Ice Sheet Complex. (15th April 2020) - Dalton, April S.; Margold, Martin; Stokes, Chris R.; Tarasov, Lev; Dyke, Arthur S.; Adams, Roberta S.; Allard, Serge; Arends, Heather E.; Atkinson, Nigel; Attig, John W.; Barnett, Peter J.; Barnett, Robert L.; et al.
Abstract: The North American Ice Sheet Complex (NAISC; consisting of the Laurentide, Cordilleran and Innuitian ice sheets) was the largest ice mass to repeatedly grow and decay in the Northern Hemisphere during the Quaternary. Understanding its pattern of retreat following the Last Glacial Maximum is critical for studying many facets of the Late Quaternary, including ice sheet behaviour, the evolution of Holocene landscapes, sea level, atmospheric circulation, and the peopling of the Americas. Currently, the most up-to-date and authoritative margin chronology for the entire ice sheet complex is featured in two publications (Geological Survey of Canada Open File 1574 [Dyke et al., 2003]; 'Quaternary Glaciations – Extent and Chronology, Part II' [Dyke, 2004]). These often-cited datasets track ice margin recession in 36 time slices spanning 18 ka to 1 ka (all ages in uncalibrated radiocarbon years) using a combination of geomorphology, stratigraphy and radiocarbon dating. However, by virtue of being over 15 years old, the ice margin chronology requires updating to reflect new work and important revisions. This paper updates the aforementioned 36 ice margin maps to reflect new data from regional studies. We also update the original radiocarbon dataset from the 2003/2004 papers with 1541 new ages to reflect work up to and including 2018. A major revision is made to the 18 ka ice margin, where Banks and Eglinton islands (once considered to be glacial refugia) are now shown to be fully glaciated. Our updated 18 ka ice sheet increased in areal extent from 17.81 to 18.37 million km 2, which is an increase of 3.1% in spatial coverage of the NAISC at that time. Elsewhere, we also summarize, region-by-region, significant changes to the deglaciation sequence. This paper integrates new information provided by regional experts and radiocarbon data into the deglaciation sequence while maintaining consistency with the original ice margin positions of Dyke et al. (2003) and Dyke (2004) where new information is lacking; this is a pragmatic solution to satisfy the needs of a Quaternary research community that requires up-to-date knowledge of the pattern of ice margin recession of what was once the world's largest ice mass. The 36 updated isochrones are available in PDF and shapefile format, together with a spreadsheet of the expanded radiocarbon dataset (n = 5195 ages) and estimates of uncertainty for each interval. Highlights: Updated deglaciation sequence using regional studies/expertise and radiocarbon data. Region-by-region overview of significant ice margin changes from 18 ka to 1 ka. New 18 ka 14C (∼21.7 ka cal.) ice sheet is 3.1% larger than previous estimates. 36 updated isochrones (PDFs/shapefiles) and radiocarbon dataset (n = 5195 ages). Ice margins of Dyke et al. (2003) retained where new information is lacking.